The development of a standardized production and monitoring system for Itemhound Corporation - Bautista, Karissa May B.; Daway, Gerrick Junn C.; Domingo, Cecilia Leonida N.; Perez, Jose Alvin S.
Itemhound, Inc. is a local start-up company that offers RFID services and solutions. Being one of the very first competitors in a very young local industry, the company lacks a verified, standard process for the production of its products. This lack of an effective and efficient standardized process result to high defects rate which then result to significant costs and lost revenue. Additionally, new competitors are entering the industry and threatening to gain significant market share over the next few years. In this regard, the group performed the study to identify and address the problems of the company with the goal of helping them to develop their process and further improve their business. To do this, the group performed root cause analysis using Stream Diagnostics in order to identify the biggest cause of the problems. Next the group explored and developed 6 alternative processes that the company could take in order to improve their process and minimize their defect rates. The group then compared these alternatives using Breakeven Analysis to identify at which production levels these alternatives most applicable. Using their current production level, the group then proposed the procurement of an RFID Printer and use of outsourced lamination to allow for the use of a cheaper paper. To further reduce defect rates in proposed recommendation, the group then performed standardization through the use of SOP's. To record and monitor the process, as well as, detect potential problems and defects the group also recommended the use of Statistical Process Control. The group also developed measures to prevent process alterations and defects using Jidoka. Lastly, the group recommends the use of 5S for Housekeeping to minimize inefficiencies and time for searching tools. To analyse the recommendations based on their potential costs, the group performed a Cost-Benefit analysis to see the possible implications of implementing the recommendations. Lastly, the group developed an implementation plan to guide the company should they wish to implement some or all of the recommendations.